Leveraging Immutability to Validate Hazard Pointers for Optimistic Traversals - Lee, Janggun; Kim, Jeonghyeon; Kang, Jeehoon (Proceedings of ACM on programming languages, 2025)
Hazard pointers (HP) is one of the earliest manual memory reclamation algorithms for concurrent data structures. It is widely used for its robustness: memory overhead is bounded (e.g., by the number of threads). To access a node, threads first announce the protection of each to-be-accessed node, which prevents its reclamation. After announcement, they validate the node's reachability from the root to ensure that no threads have missed the announcement and reclaimed it. Traversal-based data structures typically takes a marking-based validation strategy. This strategy uses a node's mark to indicate whether the node is to be detached. Unmarked nodes are considered safe to traverse as both the node and its successors are still reachable, while marked nodes are considered unsafe. However, this strategy is inapplicable to the efficient optimistic traversal strategy that skips over marked nodes. We propose a new validation strategy for HP that supports lock-free data structures with optimistic traversal, such as lists, trees, and skip lists. The key idea is to exploit the immutability of marked nodes, and validate their reachability at once by checking the reachability of the most recent unmarked node. To ensure correctness, we prove the safety of Harris's list protected with the new strategy in Rocq using the Iris separation logic framework. We show that the new strategy's performance is competitive with state-of-the-art reclamation algorithms when applied to data structures with optimistic traversal, while remaining simple and robust.